Modelling of four bay nine-storey tunnel form building using Ruaumoko 2D program / Najia Karimi - Karimi, Najia (2018)
Four bay nine-storey tunnel form building with reinforced concrete rigid shear walls had been designed using STAAD PRO V8i program in accordance to British Code (BS8110) and modelled using Ruaumoko 2D under seven past earthquake excitations. These ground motions are the 1986 Mexico City Earthquake, the Norway Earthquake, the 1940 EL-Centro North South Earthquake, the Grace Earthquake, the 1971 Pacoima Dam Earthquake, the 1940EL-Centro East West Earthquake and the 2007 Bukit Tinggi Earthquake. The four bay nine-storey tunnel form building had been modelled and run under seven past ground motions records based on time history-analysis by considering the nonlinear behaviour of the construction materials.